Quark Models of the Nucleon–Nucleon Interaction - Fernández, Francisco; Ortega, Pablo G.; Entem, David R. (Frontiers in Physics, 2020)
The present chapter aims to provide a review on the relevance of quark degrees of freedom in the description of the nucleon-nucleon and, in general, of the baryon-baryon interaction. After an historical introduction, the second section of the chapter will be dedicated to the first attempts to describe the short-range part of the NN potential in the so-called quark potential models. Here the importance of the symmetries of the 6-quark system will be emphasized. Then, we will discuss the concept of the constituent quark mass as originated by the breakdown of the chiral symmetry, in line with the articles of MANOHAR1984189 and the Instanton Liquid Model of Diakonov:2002fq, and its consequences on the quark-quark interaction due to the presence of the Goldstone boson exchanges. Once the full quark-quark interaction is established, the description of the bound states (deuteron), the scattering states of the NN system and nuclear matter in constituent quark models will be addressed. In this part a discussion of the influence of NΔ, ΔΔ or NN^* components will be included. The rest of the chapter will be devoted to the extension of the model to other baryon-baryon system, namely the triton, hyperon-hyperon and nucleon-antinucleon systems, and references to other possible descriptions of the NN interaction in terms of quark degrees of freedom ( bag models). The chapter will end with a conclusion remarks where the success and limitations of the model described above will be summarized.